Caracterização de propriedades de uma junta soldade em liga de alumínio AA5083 - Marco, Carlos Gustavo de (2014)
Increasing globalization and technological developments have progressively demanded companies to seek cost reductions and higher competitiveness, productivity, and quality in products manufactured and marketed. The search for materials with high mechanical resistance and low weight is a mandatory requirement in this setting, and it is no different in metallurgy. Aluminum and its alloys come as great alternatives to meet those demands. Choosing a type of material that will adapt and meet the requirements imposed by aluminum-made equipment, most often occurs without a detailed study on property and process conditions. Welding is one of the most important manufacturing processes in the industry. Thus, an assessment is made of a welded joint of the alloy 5083-o, through the Automated Pulsed MIG (Metal Inert Gas) process. The aluminum welding, mentioned by Mathers, (2002) as difficult, is due to the formation of porosity in the weld bead. This work presents a study on the use of preheating to reduce porosity. The test specimens were manufactured, welded, and analyzed in welding laboratories at the University Foundation of Passo Fundo (UPF), RS, Brazil. The material used were aluminum sheets 5083-O with thickness of 6 mm, length of 250 mm, and width of 120 mm. Welding was performed in a robotic cell with an OTC SUMIG robot with OTC Digital Inverter DP 400 welding source, a device was used to attach the test specimens, and welding was performed by Ceramic Backing. Parameters of welding speed, amperage, voltage, and gas flow were kept at a fixed rate for all welds. On the other hand, preheating temperature and shielding gas were varied. The shielding gases used were 100% argon, and a mix of 75% argon and 25% helium. Test specimens were submitted to preheating at 120 ˚C, preceding each welding. The main objective of this work is to use the techniques mentioned for reducing porosity in the weld bead of specimens analyzed. The reduction of the porosity will be a parameter to increase the strength of welded joints. The porosity analysis was performed using an X-ray microtomógrafo. The test results for the reduction in porosity were satisfactory because the amount of pores was lower with use of argon and helium mixture but since the use of the preheating can not be said that it was beneficial to use the results. The mechanical strength of the joints was affected by adding material having less strength than the base metal